The clinical results of buccal advanced flap for the closure of oroantral perforations (Mustansiria Dental Journal, 2018)
Aim of this study was to evaluate the success of buccal sliding flap used in thereconstruction of oroantral defects, and clarify its indications and size limitations. Inthis prospective clinical study, buccal Sliding flap was used for closure of oroantraldefect in 23 patients with different indications which included; 4 defects resultingfrom maxillary cysts (radicular and residual cyst) ,12 newly created medium size oroantralcommunications, 7 cases with chronic oroantral fistula. The defect diameterrange between 3-8 mm. Patients were evaluated for signs of flap epithelialization,infection, and fistulae recurrence.The epithelialization process was completed in 19 patients after 2 weeks withoutany complication. However, partial dehiscence of the flap occurred in 4 patients withchronic oroantral fistula.The results of this series support the view that the use of buccal sliding flap is asimple, convenient, and reliable method for the reconstruction of small to mediumsizedoroantral defects with minimum complications.